A complicated case of monkeypox and viral shedding characteristics. Issue 1 (January 2023) - Kapmaz, Mahir; Uymaz, Derya Salim; Ozcan, Gulin; Barlas, Tayfun; Guney-Esken, Gulen; Manici, Mete; Keske, Şiran; Kuşkucu, Mert; Can, Füsun; Ergönül, Önder
Highligths: Management of a monkeypox case complicated with anal abscess relieved by colostomy. The viral load and viable virus was highest in skin pustule and rectal smears. Prolonged viable virus was detected in nasopharynx until 21th day of onset of symptoms. No viable virus was detected in the patient room air, which provokes the re-consideration of using N95 respirators for daily caregivers.